The Formative Stage of Picasso in Galicia - Zurrón López, Inmaculada (Madrygal. Revista de Estudios Gallegos, 2015)
This article recognizes the importance of Picasso’s brief five year stay in A Coruña, being the place where he began his artistic studies. Through the narration of the events experienced by the artist in Galicia, the objective of this text is to compare his work at that time with his later paintings. In both stages one can appreciate similarities in composition and the use of colour.